Pose method technique improves running performance without economy changes - Fletcher, G.; Romanov, N.; Bartlett, R. (International Journal of Sports Science and Coaching, 2008)
The aim was to investigate the affects of the Pose® method intervention on running technique, on economy and a time-trial runs. A 2 x 2 mixed factorial ANOVA assessed sixteen research variables where group (Heel-toe vs. Pose®) and trial (pre to post changes) was used. Significant interactions were explored using Tukey post hoc tests, which found significance (Pose® runners pre-post test) for stance time (p = 0.001), horizontal displacement of the centre of mass to support foot at 25 ms after impact (p = 0.042), centre of mass displacement during stance (p = 0.001), knee flexion angular velocity during stance (p = 0.005) and during swing to maximum knee flexion (p = 0.043) and stride frequency (p = 0.002). The Pose® group`s post-test time-trial (2400 m) was not significant yet they improved by a mean of 24.7 s compared with a 3 s decrease in the heeltoe group. No significant changes pre-post test, were found for an economy run (2400 m) at 3.35 m/s.